2018
DOI: 10.3389/fmicb.2018.02210
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Staphylococcus aureus Bacteremia: Association of Molecular Factors With the Source of Infection

Abstract: Staphylococcus aureus bacteremia (SAB) is associated with high morbidity and mortality, which varies depending on the source of infection. Nevertheless, the global molecular epidemiology of SAB and its possible association with specific virulence factors remains unclear. Using DNA microarrays, a total of 833 S. aureus strains (785 SAB and 48 colonizing strains) collected in Spain over a period of 15 years (2002–2017) were characterized to determine clonal complex (CC), agr type and repertoire of resistance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
39
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 50 publications
9
39
3
Order By: Relevance
“…The molecular epidemiology of MRSA in bloodstream infections has been described previously, but less frequently in respiratory infections contracted in the ICU [27,28]. CC22 is one of the largest circulating clonal complexes associated with hospital-acquired MRSA in Europe (UK) and Asia (Kuala Lumpur, China) [11,29], while studies of nosocomial pneumonia indicate that CC5 is associated with MRSA strains originating mostly from the US, Europe (Portugal), Asia (China), Africa (Algeria) and Latin America (Argentina and Chile) [18,19,30,31].…”
Section: Discussionmentioning
confidence: 87%
“…The molecular epidemiology of MRSA in bloodstream infections has been described previously, but less frequently in respiratory infections contracted in the ICU [27,28]. CC22 is one of the largest circulating clonal complexes associated with hospital-acquired MRSA in Europe (UK) and Asia (Kuala Lumpur, China) [11,29], while studies of nosocomial pneumonia indicate that CC5 is associated with MRSA strains originating mostly from the US, Europe (Portugal), Asia (China), Africa (Algeria) and Latin America (Argentina and Chile) [18,19,30,31].…”
Section: Discussionmentioning
confidence: 87%
“…It has been suggested that CC5 has become an increasingly frequent cause of MRSA infections as well as bacteremia acquired by hospitalized patients from some other reports and that healthcare exposure is no longer a discriminator of USA100 vs USA300 infections [28][29][30] . An analysis of SAB conducted in www.nature.com/scientificreports www.nature.com/scientificreports/ Spain over 15 years (2002-2017) revealed that CC5 was the most prevalent CC and the proportion of CC5 among healthcare-associated S. aureus isolates was higher than that among community-associated S. aureus isolates, and CC5 was much more associated with methicillin resistance 4 . Simultaneously, CC5 MRSA was also prevalent in bloodstream infections in nine Latin American countries except in Colombia and Ecuador 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of patients with LA-MRSA CC398 BSIs had no history of exposure to livestock, which is similar to the ratio observed for other types of MRSA, and it demonstrates that the increase of LA-MRSA CC398 BSIs was accompanied by a large increase of LA-MRSA CC398 SSTIs and the expansion of porcine reservoir 32 . CC398 S. aureus resulted in an increasing incidence of bloodstream infections tst (21),sea (4),seb (1),sec (21),seg (24),seh (15),sei (22) tst (1), sec (1), seg (1), sei (1) sed (3), seg (3), seh (1),sei (3), sej (2) 764 12 2 II (8) IV (2) t002 (8) t002 (2) t002 (2) tst (3),seb (2),sec (3), seg (8),seh (8),sei (8) tst (2), sec (2), seg (2), seh (2), sei (2) sec (1), sed (1), seg (2), seh (1), sei (2) www.nature.com/scientificreports www.nature.com/scientificreports/ in a French hospital between 2010 and 2017 as well; the prevalence rate of CC398 isolates among S. aureus BSIs increased from 3.6% in 2010 to 20.2%in 2017 (P < 0.05) 33 . CC398 MRSA emerged but remains very sparse and CC398 MSSA disseminates in the community as suggested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hsdM gene has recently been shown to be a hotspot for chromosome rearrangements in staphylococcus causing phenotype switching associated with persistent infections (17). The clfA gene, which mediates staphylococcal binding to brin coated surfaces, has previously been linked to bacteraemia (18).…”
Section: Gwas For Bacteraemia Vs Non-bacteraemia Mrsamentioning
confidence: 99%